Role of antioxidants in facilitating the body functions: A review - Kiran Kumar Kattappagari; C S Ravi Teja; Radhika Kalyani Kommalapati; Chandrashekar Poosarla; Sridhar Reddy Gontu; Baddam Venkata Ramana Reddy (Wolters Kluwer Medknow Publications, 2015)
The cell damage will cause the release of free radicals. These free radicals will play an important role in any bioactive process of the cells. Antioxidants are one of the important components which plays a critical role to maintain the cell functioning and integrity of the cells. Antioxidants play an important role against the reactive oxygen species and maintain the normal activity of the cell. Antioxidants are preventing the free radical configuration tissue damage by preventing the formation of radicals or promoting their breakdown of free radical species. The review article explains the role of antioxidants in normal healthy conditions as well as diseases.